Considerations for ultra-endurance activities: part 2 - hydration - Hoffmann, M. D.; Stellingwerff, T.; Costa, R. J. S. (Research in Sports Medicine, 2019)
It is not unusual for those participating in ultra-endurance (> 4 hr) events to develop varying degrees of either hypohydration or hyperhydration. Yet, it is important for ultra-endurance athletes to avoid the performance limiting and potentially fatal consequences of these conditions. During short periods of exercise (< 1 hr), trivial effects on the relationship between body mass change and hydration status result from body mass loss due to oxidation of endogenous fuel stores, and water supporting the intravascular volume being generated from endogenous fuel oxidation and released with glycogen oxidation. However, these effects have meaningful implications during prolonged exercise. In fact, body mass loses well over 2% may be required during some ultra-endurance activities to avoid hyperhydration. Therefore, the typical hydration guidelines to avoid more than 2% body mass loss do not apply in ultra-endurance activities and can potentially result in hyperhydration. Fortunately, achieving the balance of proper hydration during ultra-endurance activities need not be complicated and has been well demonstrated to generally be achieved by simply drinking to thirst and avoiding excessive sodium supplementation with intention of replacing all sodium losses during the exercise. Abstract from author